2017
DOI: 10.5466/ijoms.15.85
|View full text |Cite
|
Sign up to set email alerts
|

<b>Importance of Professional Oral Hygiene in Preventing Medication-related Osteonecrosis of the Jaw </b>

Abstract: It has been reported that bisphosphonate treatment induces medication-related osteonecrosis of the jaw (MRONJ). Although dental extraction, periodontal disease and systemic disease are noted as risk factors for MRONJ, there are few reports examining the relationship between oral hygiene and MRONJ. The purpose of this retrospective study was to determine risk factors for MRONJ occurrence, and to assess whether MRONJ occurrence is suppressed by professional oral hygiene management or not.The participants were pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Other studies suggest that impeccable oral hygiene and limited surgical intervention may allow some mitigation of the progression of the disease [30,31]. These observations suggest that it is not only exposure to bisphosphonates that determines the progression of the disease, but also the metabolic activity within the bone and the surrounding oral and extra-oral tissue environment (including the blood supply) which determine the onset and progression of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies suggest that impeccable oral hygiene and limited surgical intervention may allow some mitigation of the progression of the disease [30,31]. These observations suggest that it is not only exposure to bisphosphonates that determines the progression of the disease, but also the metabolic activity within the bone and the surrounding oral and extra-oral tissue environment (including the blood supply) which determine the onset and progression of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of oral hygiene has also been well-recognized since Yoneyama et al (1) reported that good oral hygiene prevents aspiration pneumonia in the elderly. In particular, the preventive effects of perioperative oral management and infection control have also been reported in patients with medication-related osteonecrosis of the jaw and in those undergoing surgical therapy, chemotherapy, and radiation therapy for malignant tumors (2)(3)(4)(5). Denture plaque control (i.e., denture cleaning) is essential for maintaining oral hygiene in patients who wear dentures.…”
Section: Introductionmentioning
confidence: 99%